2012
DOI: 10.1590/s0103-50532012000700003
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterisation and evaluation of brazilian clay-based catalysts for use in esterification reactions

Abstract: Catalisadores a base de argilas naturais brasileiras foram preparados, caracterizados, e sua atividade catalítica foi avaliada em reações de esterificação. As argilas naturais foram ativadas por tratamento ácido como recebidas, sem qualquer tratamento prévio. As argilas naturais e as argilas ácidas foram caracterizadas por DRX, TPD-NH 3 , termodessorção de n-butilamina, análise de adsorção de N 2 , FT-IR, TGA e DTA. O desempenho catalítico foi investigado em reações de esterificação de diversos ácidos carboxíl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…For the lower sintering temperature of 1300 • C, well-crystallized mullite peaks were observed for both pure undoped and vanadia doped alumina porcelain. The diffraction peak of cristoballite (2Â = 20.8 • ) [31] was also observed at 1300 • C but it disappears after sintering at 1500 • C. At 1300 • C, mullite formation was enhanced with increase in vanadium pentoxide. This is due to the fact that V 2 O 5 melts at 700 • C resulting in lowering of viscosity of SiO 2 rich liquid phase and hence facilitating the interaction between SiO 2 and Al 2 O 3 .…”
Section: X-ray Diffraction Analysismentioning
confidence: 90%
“…For the lower sintering temperature of 1300 • C, well-crystallized mullite peaks were observed for both pure undoped and vanadia doped alumina porcelain. The diffraction peak of cristoballite (2Â = 20.8 • ) [31] was also observed at 1300 • C but it disappears after sintering at 1500 • C. At 1300 • C, mullite formation was enhanced with increase in vanadium pentoxide. This is due to the fact that V 2 O 5 melts at 700 • C resulting in lowering of viscosity of SiO 2 rich liquid phase and hence facilitating the interaction between SiO 2 and Al 2 O 3 .…”
Section: X-ray Diffraction Analysismentioning
confidence: 90%
“…1. As seen, MMT exhibited the XRD characteristic peaks around 2θ 5.9 indicating the smectite 24 and 2θ 20, 22 and 36 . It was reported that the peak at 2θ 21.8 having basal distance of 4.08Å is the impurities such as cristobalite and tridimite remaining in the MMT after acid treatment 25 .…”
Section: Catalyst Characterizationmentioning
confidence: 78%
“…1. It can be seen that the characteristic peaks at 2θ 5.9, 20, 22 and 36 were assigned to the smectite 25 . In the MMT after acid treatment, it was informed that the peak at 2θ 21.8 having basal distance of 4.08 Å is the impurities 21 .…”
Section: Characteristicsmentioning
confidence: 98%